Critical success factors of small and medium-sized enterprises in Saudi Arabia: Insights from sustainability perspective - Ahmad Al-Tit; Anis Omri; Jalel Euchi (Administrative Sciences, 2019)
The aim of this study is to explore the critical success factors (CSFs) of small and medium-sized enterprises (SMEs) in Saudi Arabia. A questionnaire was developed using 28 factors/indicators identified from the previous researches. From 500 respondents, a total of 347 questionnaires were returned. By conducting exploratory factors analysis, these indicators were categorized into six factors, namely: Individual factors, business characteristics, management factors, business support, capital availability and business environment. Using IBM SPSS and AMOS, the results indicated that business support was the most critical factor that significantly affects the success of SMEs in Saudi Arabia, followed by individual factors, capital availability, and management factors. They also indicated that business characteristics and business environment factors had no significant impacts on the success of these enterprises.
Keywords: 350; critical success factors; business support; corporate social responsibility; SMEs; Saudi Arabia